2012
DOI: 10.1182/blood-2012-01-402453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic epigenetic enhancer signatures reveal key transcription factors associated with monocytic differentiation states

Abstract: Cellular differentiation is orchestrated by lineage-specific transcription factors and associated with cell type-specific epigenetic signatures. In the present study, we used stage-specific, epigenetic "fingerprints" to deduce key transcriptional regulators of the human monocytic differentiation process. We globally mapped the distribution of epigenetic enhancer marks (histone H3 lysine 4 monomethylation, histone H3 lysine 27 acetylation, and the histone variant H2AZ), describe general properties of marked reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
163
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(180 citation statements)
references
References 49 publications
17
163
0
Order By: Relevance
“…It is involved in both transcriptional activation and suppression, and recent evidence has implicated C/EBPb in the transcriptional silencing of miRNAs such as let-7i, miR-145, and miR-155 (53,63). Accessibility of promoters to C/EBPb depends on H3 methylation status at the C/EBPb binding region, as demonstrated previously (64,65). Indeed, H3 methylation was detected in the proximal region of the miR-155 and miR-146a promoters (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…It is involved in both transcriptional activation and suppression, and recent evidence has implicated C/EBPb in the transcriptional silencing of miRNAs such as let-7i, miR-145, and miR-155 (53,63). Accessibility of promoters to C/EBPb depends on H3 methylation status at the C/EBPb binding region, as demonstrated previously (64,65). Indeed, H3 methylation was detected in the proximal region of the miR-155 and miR-146a promoters (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…An additional sample, which was not analyzed by exome sequencing and lacked acquired mutations in EGR2, clustered together with the EGR2-mutated samples, suggesting that other alterations mimic the effect of EGR2 mutations. To investigate whether the differentially expressed genes might be direct EGR2 targets, we used ChIPseq data obtained from primary human monocyte extracts via chromatin immunoprecipitation with anti-EGR2 antibodies (27). Peaks were observed close to 168 of the 224 upregulated genes, indicating that these genes were likely directly regulated by EGR2 (P < 0.001; see Supplementary Table S5 and Methods).…”
Section: Research Articlementioning
confidence: 99%
“…Detailed information on the localization, sequence characteristics of DNA targets, and associated binding partners is now available for ETS transcription factors in a range of cell types and developmental contexts. 27,[50][51][52][53][54][55] Although various levels of redundancy and specificity are observed that correlate with the ontology of the genes involved, one recurring feature is the close correspondence between in vivo and in vitro DNA sequence preferences. Moreover, in the case of PU.1 and Ets-1, the information contents (a direct informatic measure of target specificity) of the in vivo sequences preferences shown by both proteins are over 15% higher (> 3 bits over a 10-bp sequence space) than their in vitro counterparts.…”
Section: Combinatorial Routes To Ets Target Specificitymentioning
confidence: 99%
“…While the importance of epigenetic regulation of ETSdependent transcription is well established in hematopoiesis and cancer, 55,[66][67][68] the mechanisms by which ETS activity are modulated at epigenetically modified DNA, with or without nucleosome, are not well understood. Genomic surveys have found that hematopoietic ETS transcription factors are over-represented in hypermethylated regions.…”
Section: Differential Tolerance To Cpg Methylationmentioning
confidence: 99%